Preparation Training for the Implementation of Agricultural Micro Insurance in the Prosperous Farmers Group, Parungponteng Village, Tasikmalaya Regency - Yuyun Hidayat; Sukono Sukono; Titi Purwandari (International Journal of Research in Community Services, 2022)
Agriculture is a form of processing biological natural resources with the help of technology, capital, labor, and management. In Indonesia, agriculture is the main source of livelihood in some areas, one of which is Cibungur village, Parungponteng sub-district, Tasikmalaya district, West Java. With agriculture as the main livelihood in the village, all of these are not spared from the risks that can damage the agricultural sector. With the risks that can occur, there comes a solution to this problem, one of which is insurance. One of the insurance facilities for handling farmer risk is the Agricultural Micro Insurance program, which is expected to provide protection against the risk of uncertainty by providing guarantees for farmers to get working capital for farming from insurance claims. With this insurance, it can also reduce the risks that will occur which may be detrimental in the future. To realize this micro-insurance, we provide guidance to the prosperous farmer cooperative groups to form micro-insurance within the cooperative.